Assessment on society’s opinion about using psychological and psychiatric help - Zimnicki, Patryk; Zawiślak, Magdalena Kamila; Zaniuk, Marcin; Kozłowska, Marta; Kozyra, Magdalena (Journal of Education, Health and Sport, 2021)
To properly treat diseases related to the human psyche, the help of specialists in psychology or psychiatry is essential. Unfortunately, its use is often negatively perceived by society, which discourages people with mental disorders to use it. It was decided to examine the opinion of society on this issue. For this purpose, we used the original questionnaire " A Survey of public opinion on the use of psychological or psychiatric help", conducted among 238 people. The answers were statistically analyzed. The results of the questionnaire confirm the existence of the problem. In addition, more than 70% of the respondents believe that access to psychological or psychiatric help is not easy. Nearly 60% of the respondents criticized visits to a psychologist or psychiatrist, of which 37.9% were from people close to them. Only half of the respondents decided to use the help of a specialist, and 78% of them felt fear before the visit, associated with the diagnosis (33.6%), the ineffectiveness of therapy (25%), and the opinion of relatives (9.5%). Despite this, only 5.2% experienced a negative perception. The analysis of the literature indicates a large role of stigmatization of people with mental disorders as a factor influencing the occurrence of reluctance to seek help from psychologists or psychiatrists. The influence of gender and age on this state of affairs has also been noted. Increasing social awareness of the positive aspects of seeking help from psychologists or psychiatrists can significantly change public opinion on this issue. This can bring many benefits to people struggling with mental health problems, as well as reduce their fear of visiting a specialist.